MODERN OPPORTUNITIES OF USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN GYNECOLOGY (Multidisciplinary Journal of Science and Technology, 2026)
In modern medicine, the introduction of digital technologies, in particular artificial intelligence (AI) systems, is gaining importance in gynecological practice. In maintaining women's reproductive health, early detection and effective treatment of gynecological diseases, artificial intelligence technologies allow increasing the accuracy of diagnosis and improving the quality of medical services. This article scientifically analyzes the areas of application of artificial intelligence in gynecology, its importance in the diagnostic and treatment process, its advantages and existing problems.